1990
DOI: 10.1080/03079459008418706
|View full text |Cite
|
Sign up to set email alerts
|

Type a influenza viruses in birds in southern Spain: Serological survey by enzyme‐linked immunosorbent assay and haemagglutination inhibition tests

Abstract: SUMMARYOf 927 sera taken from poultry from 84 flocks, 33% proved seropositive. Sixtythree per cent of flocks were found to be seropositive to ELISA (almost all situated within areas where there were waterfowl). The comparable figures, using an HI test, were 16% and 47%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Out of the 67 non-specific serum samples, 4 samples were shown to be positive by blocking ELISA. This is in accordance with the result of Adair et al [14] and Arenas et al [15], who reported that the ELISA test is better than HI test.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Out of the 67 non-specific serum samples, 4 samples were shown to be positive by blocking ELISA. This is in accordance with the result of Adair et al [14] and Arenas et al [15], who reported that the ELISA test is better than HI test.…”
Section: Discussionsupporting
confidence: 82%
“…Besides, 4 samples giving HI titer <1:80 in HI tests were also gave positive result in the ELISA test. This depicts the sensitivity of ELISA is higher than that of HI test as found in the case of Adair et al [14] and Arenas et al [15]. Contrary to this result, Zhou et al (1998) and Sala et al [16] reported higher sensitivity of HI test over the ELISA test.…”
Section: Discussioncontrasting
confidence: 52%
“…The latter is consistent with patterns observed in Europe (Arenas et al, 1990;Astroga et al, 1994;De Marco et al, 2003), and North America (Brown et al, 2010) among wintering waterbirds. The prevalence of AI virus in a population is highly variable and is dependent on host species, season, geographic location and age.…”
supporting
confidence: 86%
“…The AGID test produces inconsistent results in waterfowl hosts and, consequently, has been considered to be a serologic assay with limited use in wildbird AI surveillance (Stallknecht et al, 2007). Multiple studies have utilized various indirect or bELISAs to detect type-specific antibodies to AI viruses in wild waterbirds from Spain (Arenas et al, 1990;Astorga et al, 1994), Italy (De Marco et al, 2003), and the USA (Sullivan et al, 2009). In this study, antibodies to AI virus were detected in the majority of Argentinean waterfowl species that were tested with the bELISA (Table 1).…”
mentioning
confidence: 84%